2016
DOI: 10.1371/journal.pone.0155608
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of More Lymph Nodes in Colon Cancer Is Associated with Improved Survival in Patients of All Ages

Abstract: BackgroundImprovement in survival of patients with colon cancer is reduced in elderly patients compared to younger patients. The aim of this study was to investigate whether the removal of ≥ 12 lymph nodes can explain differences in survival rates between elderly and younger patients diagnosed with colon cancer.MethodsIn a population-based cohort study, all patients (N = 41,074) diagnosed with colon cancer stage I to III from 2003 through 2010 from the Netherlands Cancer Registry were included. Age groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…For example, fifteen studies did not report the time origin from which the survival time had been calculated 16,20,26,2832,35–37,41,43,51,52 , and six studies did not indicate the end of follow-up date 29,35,36,41,44,52 . In 28 articles the authors did not report follow-up time 1621,2631,35,37–44,46,48,5254 , and the number of deaths were missing in 26 artides 16,1821,2732,35,37–41,43,44,48,49,5254 only three studies reported the source of age at diagnosis (from medical records) 27,3044 . In seven studies, the authors did not provide numerical survival estimates 1619,21,26,46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, fifteen studies did not report the time origin from which the survival time had been calculated 16,20,26,2832,35–37,41,43,51,52 , and six studies did not indicate the end of follow-up date 29,35,36,41,44,52 . In 28 articles the authors did not report follow-up time 1621,2631,35,37–44,46,48,5254 , and the number of deaths were missing in 26 artides 16,1821,2732,35,37–41,43,44,48,49,5254 only three studies reported the source of age at diagnosis (from medical records) 27,3044 . In seven studies, the authors did not provide numerical survival estimates 1619,21,26,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Only one study analysed a random sample of patients 26 . Of seventeen studies examining colon cancer, five studies aimed at investigating age disparities in colon cancer survival (Table 2) 16,17,31,32,34 . Six studies used data from The Netherlands 16,17,21,27,30,32 , and five presented data from the U.S.A. 26,31,33,3454 .…”
Section: Resultsmentioning
confidence: 99%
“…Hoehn et al 14 found that patients were less likely to have their lymph nodes examined if they were treated at CCCs, which may explain the lower OS. Studies in colon cancer have confirmed that the evaluation of more lymph nodes is associated with improved survival due to more accurate staging 15 …”
Section: Discussionmentioning
confidence: 97%
“…Colorectal cancer is the third most common cancer worldwide with a high rate of morbidity and mortality (1). Each year, there are over one million newly diagnosed cases and approximately 600,000 cases of colorectal cancer-associated mortality (2). The major risk factors of colorectal cancer are increasing age and lifestyle factors, and other risk factors include obesity, insulin resistance and metabolic syndrome (3).…”
Section: Introductionmentioning
confidence: 99%
“…The major risk factors of colorectal cancer are increasing age and lifestyle factors, and other risk factors include obesity, insulin resistance and metabolic syndrome (3). The survival of this disease has improved considerably, however, the 5-year relative survival for patients aged 65 years and older remains as low as 60% (2). An improved understanding of the underlying mechanisms of colorectal cancer may provide valuable information for treating this disease.…”
Section: Introductionmentioning
confidence: 99%